2000
DOI: 10.1002/1099-1573(200009)14:6<401::aid-ptr762>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring antinociceptive substances from plants

Abstract: Despite the progress that has occurred in recent years in the development of therapy, there is still a need for effective and potent analgesics, especially for the treatment of chronic pain. One of the most important analgesic drugs employed in clinical practice today continues to be the alkaloid morphine. In this review, emphasis will be given to the important contribution and the history of Papaver somniferum, Salix species, Capsicum species and Cannabis sativa in the development of new analgesics and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 112 publications
0
55
0
1
Order By: Relevance
“…Hesperidin showed marked antinociception in mice against the nociception caused by i.p. injection of acetic acid (Calixto et al, 2000).…”
Section: Review Of Known Biological Effects Of the Plants And Their Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Hesperidin showed marked antinociception in mice against the nociception caused by i.p. injection of acetic acid (Calixto et al, 2000).…”
Section: Review Of Known Biological Effects Of the Plants And Their Cmentioning
confidence: 99%
“…Caffeine alone is used for respiratory depression in neonates and to treat postprandial hypotension. The analgesic adjuvant properties of caffeine in combination with aspirin-like drugs in treating pain is attributed to the blockade of peripheral and central adenosine receptors involved in the regulation of pain transmission (Calixto et al, 2000).…”
Section: Review Of Known Biological Effects Of the Plants And Their Cmentioning
confidence: 99%
“…It is important to mention that several pre-clinical and clinical studies have demonstrated the analgesic potential of different types of flavonoids [34,52], and orientin, which is present in high amounts in the plant, might be used to obtain new and promising derivatives with an analgesic profile. The potent antinociceptive effect of orientin may explain, at least partially, the beneficial effects of foods, tea or juice which have this compound in their composition [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies have shown that the flavonoids quercetin, quercitrin and hyperoside possess antinociceptive effects when tested individually [33][34][35], it is possible that the flavonoids present in the methanol extracts and butanol fraction of this species may be responsible, at least in part, for the antinociceptive effects reported here. On the other hand, since the benzophenone derivatives were detected as major compounds in the chloroform fraction and their subfractions, it can be hypothesized that these compounds may be also associated with the effects found in the present study.…”
Section: Discussionmentioning
confidence: 99%